Lithium enrichment in the Galaxy: A study using the GALAH and Gaia surveys. Issue Volume 14:Issue S353(2019) (June 2019) - Deepak,; Reddy, Bacham E.
Abstract: Here, we explore the enrichment of Lithium in the Galaxy using a large sample of stars common among large spectroscopic surveys such as the GALAH and astrometric survey by the Gaia satellite. For this study we used about 60, 000 low mass ( M ⩽ 2M⊙ ) dwarfs from the GALAH survey. Further, we discuss Li enrichment among giant stars based on a sample of 52, 000 low mass giants, of which 335 are Li-rich with A(Li) ⩾ 1.80 ± 0.14 dex, culled from the GALAH survey. These low mass giants appears to be one of the promising source of Li enrichment in the Galaxy as their atmospheric Li can be added to the ISM through mass loss.